Function of the Classical and Alternate Pathways of Human Complement in Serum Treated with Ethylene Glycol Tetraacetic Acid and MgCl(2)-Ethylene Glycol Tetraacetic Acid - Des Prez, R. M. (1975)
An immunochemical and functional analysis of the classical and alternate complement pathways in human serum was performed in the presence of 10 mM ethylene glycol tetraacetic acid (EGTA) and MgCl(2)-EGTA (MgEGTA), chelating agents which have been recently utilized as a means of distinguishing between these two complement pathways. Total hemolytic activity, integrity of the C1 complex, hemolytic activity of C2, conversion of factor B (C3 proactivator), and complement-dependent bactericidal activity were studied. The effect of these chelators on activation of complement pathways by Escherichia coli, by sensitized erythrocytes as a prototype of activators of the classical pathway, and by zymosan as a prototype of alternate (properdin) pathway activators was studied. Human serum containing 10 mM EGTA, which provides almost no ionized calcium and considerably less ionized magnesium than unchelated serum, allowed consumption of complement via the alternate (properdin) pathway, but blocked the classical pathway as judged by disintegration of the C1 complex and lack of utilization of C2. However, activity of the alternate complement pathway in EGTA serum, as judged by conversion of factor B and bactericidal activity against gram-negative bacteria, was distinctly suboptimal. Addition of magnesium ion in a concentration equimolar to EGTA (MgEGTA serum), while still providing conditions in which the C1 complex dissociated, significantly enhanced alternate complement pathway-mediated bactericidal activity. However, in MgEGTA serum considerable fluid-phase activation of the alternate pathway, as indicated by decrease in 50% hemolytic complement (CH(5 0)) titers and conversion of factor B to its active form in the absence of any activating challenge, was observed. Moreover, some fluid-phase consumption of C2 was observed in MgEGTA serum, even though, as mentioned, the C1 complex was shown to be dissociated under these conditions. MgEGTA-related activation of C2 and of the alternate (properdin) pathway of complement was significantly enhanced by the presence of zymosan and E. coli. These results indicate that use of the chelating agents EGTA and MgEGTA to differentiate between classical and alternate pathway activation of human complement is more complex than has hitherto been suggested. In EGTA serum, spontaneous activation of either pathway does not occur but bactericidal activity, as a measure of biologic function of complement, is suboptimal. In MgEGTA serum, bactericidal activity is fully expressed, but there is considerable instability, in terms of fluid-phase activation, in Mg(2+)-dependent components of both pathways. Thus, caution is indicated in the use and interpretation of the effects of these chelating agents on biologic functions mediated by either pathway of human complement.